Clinico-Epidemiological Aspects of Telogen Effluvium In Iraqi Women - Fadheel, Basman M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: telogen effluvium is a form of non- scarring alopecia characterized by diffuse hair shedding, often of acute onset. It’s a reactive process caused by metabolic or hormonal stress or by medications. Generally, recovery is spontaneous within 6 months. Objectives: is to shed a light on the clinic- epidemiological aspects and most important causes of telogen effluvium in Iraqi women. Patients and methods: A total number of 100 female patients were seen in the period between March 2014 to March 2015 in the Dermatology Department of Baghdad Teachinhg Hospital / Medical City. Their ages ranged between 20 to 40 years old and the duration of their complaints ranged between 1 to 12 months. Their symptoms were excessive hair loss, diffuse shedding, scalp hair thinning and trichodynia. In all patients the diagnosis was confirmed by positive pull test, and the patients were questioned about all possible triggering factors. Results: In most of cases, 74%,the duration of illness was less than 6 months . all the patients complained of diffuse shedding , 12% had visibile scalp thinning and only 8% had trichodynia . In 32% of cases no underlying triggering factor was identified and 21% of cases had acute psychological distress. Conclusion: most of cases of telogen effluvium in Iraqi women were without clear underlying triggering factor, most patients were anxious about impending baldness, but significant hair thinning was present in only minority of patients. Searching for underlying iron diffeciency is important as 6% of patients had evidence of subcinical iron diffeciency on laboratory examinations.